Strategi Sosialisasi Pemilihan Kepala Daerah terhadap Generasi Z : (Studi Kasus: Komisi Pemilihan Umum Kota Tanjungpinang Tahun 2024) - Yesica Elonika; Bismar Arianto; Uly Sophia (Perspektif Administrasi Publik dan hukum, 2025)
Socialization in regional head elections is a strategy that includes the dissemination of information and materials that can raise voter awareness, especially among the younger generation which is currently dominated by Generation Z. Therefore, this study aims to determine the strategy for socializing regional head elections for generation z by the Tanjungpinang City General Election Commission in 2024. The research method used in this study is qualitative research with a case study approach. This study uses the theory of socialization proposed by Michael Rush and Philip Althoff, with theory indicators, namely socialization agents, socialization materials, socialization mechanisms, and socialization patterns. The findings of researchers from the strategy for socializing regional head elections carried out by the Tanjungpinang City KPU are quite good because the Tanjungpinang City KPU has carried out its role as an election organizer with several socialization activities. (1) socialization agents, as KPU agents carry out their roles and contribute to socialization activities, but do not involve Generation Z in them enough (2) socialization materials, the materials provided by the KPU are easy to accept and interesting according to Generation Z. (3) socialization mechanism, generation z considers the mechanism implemented by the Tanjungpinang City KPU to be quite good (4) the socialization pattern has sufficiently influenced generation z in their understanding of elections.